Respostas

A melhor resposta!
2013-06-27T22:49:36-03:00
  • Usuário do Brainly
2013-06-27T23:49:33-03:00

1) \dfrac{1-\sqrt{3}}{\sqrt{3}}

 

Temos que:

 

\dfrac{1-\sqrt{3}}{\sqrt{3}}=\dfrac{1-\sqrt{3}}{\sqrt{3}}\cdot\dfrac{\sqrt{3}}{\sqrt{3}}=\dfrac{\sqrt{3}}{\sqrt{3}}=\dfrac{\sqrt{3}-3}{3}

 

 

2) \dfrac{3-\sqrt{2}}{\sqrt{2}}

 

Analogamente, temos:

 

\dfrac{3-\sqrt{2}}{\sqrt{2}}=\dfrac{3-\sqrt{2}}{\sqrt{2}}\cdot\dfrac{\sqrt{2}}{\sqrt{2}}=\dfrac{3\sqrt{2}-2}{2}

 

 

3) \dfrac{\sqrt{5}+\sqrt{2}}{\sqrt{5}}

 

Temos que:

 

\dfrac{\sqrt{5}+\sqrt{2}}{\sqrt{5}}=\dfrac{\sqrt{5}+\sqrt{2}}{\sqrt{5}}\cdot\dfrac{\sqrt{5}}{\sqrt{5}}=\dfrac{5+\sqrt{10}}{5}

2 5 2